Higher order risk preferences: New experimental measures, determinants and field behavior - Sebastian O. Schneider; Matthias Sutter (Max Planck Institute for Research on Collective Goods, 2020)
We use a novel method to elicit and measure higher order risk preferences (prudence and temperance) in an experiment with 658 adolescents. In line with theoretical predictions, we find that higher order risk preferences - particularly prudence - are strongly related to adolescents' field behavior, including their financial decision making, eco-friendly behavior, and health status, including addictive behavior. Most importantly, we show that dropping prudence and temperance from the analysis of students' field behavior would yield largely misleading conclusions about the relation of risk aversion to these domains of field behavior. Thus our paper puts previous work that ignored higher order risk preferences into an encompassing perspective and clarifies which orders of risk preferences can help understand field behavior of adolescents.
Keywords: C93; D81; D91; J13; 330; Higher order risk preferences; prudence; temperance; risk aversion; field behavior; adolescents; health; addictive behavior; smartphone addiction; experiment